EFFECTIVENESS OF ANTAGONISTIC FUNGI Gliocladium sp. AND Trichoderma harzianum TO CONTROL Colletotrichum spp. on chili (Capsicum annuum L.) - Siti Dailah; Mofit Eko Poerwanto; Supono Budi Sutoto (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2020)
The productivity of chili in terms of both quality and quantity is suppressed by the attacks of anthracnose disease caused by Colletotrichum spp. Pesticides is commonly used to control the disease. Researched was conducted to determine the antagonistic fungi and the effective dose in inhibiting the growth of the Colletotrichum spp. Antagonistic tests were performed in vivo using the direct method with three replicates. Inhibition test was arranged in a Complete Randomized Block Design (RCBD) with 7 treatments: Control, Gliocladium sp (150, 250, and 350 mL/plant) and T. harzianum (150, 250, and 350 mL/plant) with four replicates and three samples out of 20 plants per treatment. The results showed that the percentage of inhibition of T. harzianum against Colletotrichum sp. is 55% while Gliocladium sp. is 70.33% in antagonistic test. The mean of disease intensity at 11 up to 32 DAI on control is 5.61 ± 0.71% up to 20.30 ± 1.35 % respectively. It is significantly higher than Gliocladium sp. 350 mL/Plant (1.94 ± 0.45 % up to 11.15 ± 0.87 %), T. harzianum 350 mL/Plant (1.10 ± 0.58 % up to 8.68 ± 0.91 %), and T. harzianum 250 mL/Plant (2.28 ± 0.43 % up to 8.75 ± 0.79 %). No significant different is observed on mean of fresh weight of red chili fruit yield per plant. T. harzianum and Gliocladium sp. fungi are effective in controlling the attack of anthracnose disease in chili. The most efficient dose to control anthracnose disease is the application of T. Harzianum or Gliocladium sp at the dose of 250 mL/plant.Key Words: Chilli, Anthracnose, Gliocladium, Trichoderma, Colletotrichum.